Intravesical foreign body in a 12-year-old boy - S., Pramod; J., Anukethan; K., Ravikiran (International Journal of Contemporary Pediatrics, 2018)
Self-insertion of foreign body in lower urinary tract is rare in children. It is commonly seen in adults. The reason for self-insertion may be accidental, due to psychiatric illness, curiosity, sexual stimulation or therapeutic in cases of stricture. Most of the cases reported are in adults. Here we present a 12-year-old child presenting with self-insertion of metallic hair pin into the lower urinary tract with symptoms of dysuria and retention of urine. X-ray and ultrasonography were diagnostic modalities which aided in the diagnosis. The child underwent successful cystoscopic removal of foreign body after thorough investigation. Post removal child underwent psychiatric evaluation. He was not suffering from any psychiatric condition. He admitted having inserted the hair pin out of curiosity. Child was passing urine in good stream at time of discharge. At six months follow up child remains asymptomatic.